2020
DOI: 10.1111/ene.14424
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of advance care planning in Parkinson's disease and atypical parkinsonian disorders: a mixed methods systematic review

Abstract: Background and purpose Advance care planning allows people to plan for their future care needs and can include medical, psychological and social aspects. However, little is known on the use, experience of and attitudes towards advance care planning in patients with parkinsonian disorders, their family carers and healthcare professionals. Methods A systematic search of online databases was conducted in April 2019 using a narrative synthesis approach with thematic analysis and tabulation to synthesize the findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…Most participants and family carers wanted to focus on living in the present and did not want to discuss the future or access information via digital health, due to fear of how their Parkinson's would progress. This is supported by findings of a recent systematic review conducted by our team, 36 which found many people with Parkinson's do not want to discuss advance care planning early and the right time depended on patient factors such as their values, goals and care needs. One recommendation was for healthcare professionals to invite people to discuss planning ahead early and regularly so that it does not happen during a crisis.…”
Section: Discussionsupporting
confidence: 61%
“…Most participants and family carers wanted to focus on living in the present and did not want to discuss the future or access information via digital health, due to fear of how their Parkinson's would progress. This is supported by findings of a recent systematic review conducted by our team, 36 which found many people with Parkinson's do not want to discuss advance care planning early and the right time depended on patient factors such as their values, goals and care needs. One recommendation was for healthcare professionals to invite people to discuss planning ahead early and regularly so that it does not happen during a crisis.…”
Section: Discussionsupporting
confidence: 61%
“…This is particularly true for patients with cognitive impairment, who may have difficulty in communication their person’s goals or preferences [ 66 ]. Furthermore, ACP can be helpful in developing a more patient-centered care plan based on the personal goals of a patient and family caregiver [ 67 ]. By now, ACP has been recognized as helpful for people with PD to declare their wishes on future care with regard to potentially occurring situations [ 56, 67–71 ], although its effectiveness has not been shown in randomized clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one might consider informing PD patients about the diagnosis and consequences of the disease in a two-tiered appointment similar to the process in oncology and ALS since this was shown to facilitate information uptake by the patients in the latter patient groups ( 8 ). Communication skills training for HCPs may be crucial to optimize these conversations ( 10 ). Additionally, by regularly actively inquiring the need for information by the HCPs regarding prespecified topics, tailored information in both oral and written form can be supplied to PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of advance care planning is possible alongside curative therapies and at any time during the disease course, sometimes even directly after communication of the diagnosis ( 8 , 9 ). However, in PD, instead of being integrated early, research suggests that, in current practice, ACP generally is not initiated before the progression of symptoms, cognitive decline, or the terminal phase of PD ( 10 ).…”
Section: Introductionmentioning
confidence: 99%